Magnitude of the anomalous geomagnetic fields - Rokityansky, I.I.; Tereshyn, A.V. (Geofizicheskiy Zhurnal, 2025)
The normalized amplitudes of the anomalous geomagnetic field variations (presented by tipper C) with period T>200 s arising around electrical conductivity anomalies have been considered. C>1 means that the secondary (induced) field is greater than the primary (inducing) one. Worldwide, the mean observed tippers are C=0.3 for coastal observatories and C=0.15 for inland ones. The maximum tippers are 1.5 for coastal and C=1.6 for inland observatories. Modeling realistic anomalies with uniform conductivity yields C up to 2.5. The larger C can arise in a non-uniform conductor due to the superchanneling effect.